2010
DOI: 10.1038/ki.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids protect renal mesangial cells from apoptosis by increasing cellular sphingosine-1-phosphate

Abstract: Neutral ceramidase (NCDase) and sphingosine kinases (SphKs) are key enzymes regulating cellular sphingosine-1-phosphate (S1P) levels. In this study we found that stress factor-induced apoptosis of rat renal mesangial cells was significantly reduced by dexamethasone treatment. Concomitantly, dexamethasone increased cellular S1P levels, suggesting an activation of sphingolipid-metabolizing enzymes. The cell-protective effect of glucocorticoids was reversed by a SphK inhibitor, was completely absent in SphK1-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Our results provide strong evidence that part of the renal protective actions of glucocorticoids can be explained by targeting SK-1, S1P 1 and S1P receptor metabolism in resident glomerular cells. Förster et al (2010) demonstrated that dexamethasone alters sphingolipid metabolism by upregulation of neutral ceramidase and SK-1 expression and activity and by this protects mesangial cells from stress-induced apoptosis via enhanced formation of intracellular S1P. In addition, we demonstrate here for the first time that dexamethasone markedly reduced the expression of S1P 1 in isolated mesangial cells and mouse glomeruli, which lead to lower S1P-induced mesangial cell migration.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Our results provide strong evidence that part of the renal protective actions of glucocorticoids can be explained by targeting SK-1, S1P 1 and S1P receptor metabolism in resident glomerular cells. Förster et al (2010) demonstrated that dexamethasone alters sphingolipid metabolism by upregulation of neutral ceramidase and SK-1 expression and activity and by this protects mesangial cells from stress-induced apoptosis via enhanced formation of intracellular S1P. In addition, we demonstrate here for the first time that dexamethasone markedly reduced the expression of S1P 1 in isolated mesangial cells and mouse glomeruli, which lead to lower S1P-induced mesangial cell migration.…”
Section: Discussionmentioning
confidence: 58%
“…Whether this could explain the reduced S1P 1 expression upon dexamethasone stimulation in renal mesangial cells is not yet proven. However, we previously reported that both, glitazones (rosiglitazone and troglitazone) and dexamethasone indeed enhance the expression and activity of SK-1 (Förster et al, 2010;Koch et al, 2012), but still have opposite effects on S1P 1…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations